Hypoglycaemia among adults with Type 2 Diabetes mellitus in a Family Medicine Clinic - Sodipo OO; Ademolu AB; Odunaye-Badmus S; Oluwatuyi EO; Odiana S (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: The prevalence of Diabetes mellitus (DM) is increasing worldwide. The complications of DM arising from hyperglycaemia are well documented and. However, there is a lack of data, poor awareness and information on hypoglycaemia in DM. Objective: To describe the prevalence and factors associated with hypoglycaemia among patients with Type 2 Diabetes mellitus (DM). Methods: This was a retrospective study of the clinical records of patients with Type 2 DM at the Family Medicine Clinic of a Nigerian teaching hospital from January 2019 to January 2020. The sociodemographic and clinical characteristics, including hypoglycaemia, Glycosylated Haemoglobin (HbA1c), Fasting and Random blood glucose, were retrieved. Results: A total number of 570 patients were assessed, with a prevalence of 43 (7.5%) of hypoglycaemia. The mean age of the patients in the study was 58.2±10.9 years (range: 36-83 years). Metformin (557; 97.7%), Sulphonylureas (377; 66.1%), Dipeptidylpeptidase -4 inhibitors (137; 24.0%) and insulin (72; 12.6%) were the most prescribed anti-diabetic medications. hypoglycaemiaA majority (29; 67.4%) of the hypoglycaemia episodes occurred in the morning, while most (24; 55.8%) of the episodes of hypoglycaemia were mild. Mean age (t= 2.35; p = 0.019), presence of hypertension (X2 = 6.92, p = 0.008) and dyslipidaemia (X2 = 7.86, p = 0.005) were associated with hypoglycaemia. Conclusions: The prevalence of hypoglycaemia in the Outpatient clinic was low, while the presence of comorbidities (hypertension and dyslipidaemia) and age were associated with hypoglycaemia. There is a need for patient education and Self-Monitoring of Blood Glucose (SMBG) to prevent complications of hypoglycaemia. hypoglycaemia